2007
DOI: 10.3171/spi.2007.6.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma metastases to the spine

Abstract: ✓Leiomyosarcoma is a rare malignant smooth-muscle tumor that rarely metastasizes to bone. It is extremely uncommon for osseous metastasis to be the initial presentation of leiomyosarcoma or to be the initial manifestation of recurrence in patients with a history of leiomyosarcoma. The authors have treated four cases of metastatic leiomyosarcoma with the lesion initially presenting in the spine, and a fifth case of disseminated leiomyosarcoma that involved the spine. In their report, they highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…However, distinguishing leiomyosarcomas from other aggressive spindle cell malignancies, particularly fibrosarcoma, malignant fibrous histiocytoma, malignant peripheral nerve sheath tumor and metastatic spindle cell carcinoma, is not always easy (24). Immunohistochemical studies are often useful in establishing the diagnosis by demonstrating the smooth muscle cell origin (3,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, distinguishing leiomyosarcomas from other aggressive spindle cell malignancies, particularly fibrosarcoma, malignant fibrous histiocytoma, malignant peripheral nerve sheath tumor and metastatic spindle cell carcinoma, is not always easy (24). Immunohistochemical studies are often useful in establishing the diagnosis by demonstrating the smooth muscle cell origin (3,8).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, patient survival times range from weeks to 13 years when leiomyosarcoma metastasizes to the spine (4). Despite numerous surgeons emphasizing that total resection of the tumor should be performed to achieve an improved prognosis (4,8,9), this was considered to be impossible in the patient in the present study. Therefore, decompressive surgery was selected as the therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the literature, we were able to find few cases of leiomyosarcoma recurrence occurring in bone. Elhammady et al [4] recently reported a case of spinal osteoblastic bone metastasis as the presenting symptom of leiomyosarcoma recurrence and reviewed six cases of leiomyosarcoma initially presented as spinal metastases. Shapiro et al [5] described a case of uterine smooth muscle tumor of uncertain malignant potential that recurred as a high-grade leiomyosarcoma in the humerus, 5 years after its successful removal by hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcoma is a rare malignant neoplasm of smooth muscle cells representing 7% of all soft-tissue sarcomas (Elhammady et al, 2007). Distant metastases arrive late in the disease and the predilection sites are lungs, liver, kidneys and skin through hematogenous dissemination.…”
Section: Introductionmentioning
confidence: 99%